Psychometric evaluation of the study interest questionnaire-short form among Chinese nursing students based on classical test theory and item response theory - Yue Yi Li; Lai Kun Tong; Mio Leng Au; Wai I. Ng; Si Chen Wang; Yongbing Liu; Liqiang Zhong; Yi Shen; Xichenhui Qiu (BMC Nursing)
Abstract Background There is currently no dedicated measurement for assessing nursing students’ study interest in China. Considering the good reliability, validity, and widespread applicability of the Study Interest Questionnaire-Short Form (SIQ-SF), the objective of this study was to validate its usage among Chinese nursing students. Methods The translation and cross-cultural adaptation rigorously followed the modified Brislin model. A cross-sectional survey was conducted using the Chinese version of the SIQ-SF and convenience sampling was employed to select nursing students. The Psychometric evaluation of the Chinese version of the SIQ-SF was conducted based on Classical Test Theory and Item Response Theory. Results A total of 1158 participants were included in the analysis. The item-level content validity index (CVI) ranged from 0.9 to 1.0, and the scale-level CVI was 0.98. In the Exploratory factor analysis, three factors with eigenvalues above 1 were identified, accounting for 62.554% of the cumulative variance. In the confirmatory factor analysis, the CMIN\DF was 5.639, the GFI was 0.953, the CFI was 0.902, and the IFI was 0.904. The Cronbach’s α coefficient of the Chinese version of the SIQ-SF was 0.70. Thirty-one participants were invited to sign the scale after two weeks. The intraclass correlation coefficient was 0.784, and that of items ranged from 0.70 to 0.819. The infit MnSQ values ranged between 0.76 and 1.51, and the outfit MnSQ values ranged between 0.72 and 1.76. The point-measure correlation value ranged between 0.30 and 0.68. The item difficulty measures ranged from − 0.66 to 1.44 logit and the individual learning interest estimations ranged from − 4.22 to 4.97 logit. DIF contrast ranged from 0.00 to 0.33 logits, with all p values greater than 0.05. Conclusions The Chinese version of the SIQ-SF demonstrated acceptable reliability and validity among Chinese nursing students and could be used to assess nursing students’ study interest in China. With the aid of this scale, teachers can gain a better understanding of nursing students’ study interests, thereby maximizing their learning effects through appropriate content and methods.